Peran Pemerintah Desa Lasara Kecamatan Namohalu Esiwa Dalam Meningkatkan Kesejahteraan Masyarakat Melalui Literasi Keuangan - Harefa, Fandi Rahmawan; Maria Magdalena Bate'e; Idarni Harefa; Aferiaman Telaumbanua (Visi Sosial Humaniora, 2024)
This research aims to reveal the role played by the Lasara Village Government in Namohalu Esiwa District in seeking to improve community welfare through financial literacy efforts. Financial literacy is considered an important tool that allows individuals to understand and manage their personal finances more effectively. In its conclusion, this research highlights the important role of the Lasara Village Government in increasing community financial literacy. Through educational programs and partnerships with financial institutions, village governments have succeeded in empowering communities to take control of their own finances, which ultimately contributes to increased prosperity and economic stability at the local level.